Progress in the development of subunit vaccines for gastrointestinal nematodes of ruminants. (December 2016) - Matthews, J. B.; Geldhof, P.; Tzelos, T.; Claerebout, E.
Summary: The global increase in anthelmintic resistant nematodes of ruminants, together with consumer concerns about chemicals in food, necessitates the development of alternative methods of control for these pathogens. Subunit recombinant vaccines are ideally placed to fill this gap. Indeed, they are probably the only valid option for the long‐term control of ruminant parasitic nematodes given the increasing ubiquity of multidrug resistance in a range of worm species across the world. The development of a subunit multicellular parasite vaccine to the point of practical application would be a groundbreaking step in the control of these important endemic infections of livestock. This review summarizes the current status of subunit vaccine development for a number of important gastrointestinal nematodes of cattle and sheep, with a focus on the limitations and problems encountered thus far, and suggestions as to how these hurdles might be overcome.